When Capital Conceal Harassment: Explaining Sexual Harassment in American Colleges and Universities Through the Lens of Cultural Capital Theory - Jiayi Zhou (Journal of Advanced Research in Education, 2025)
This paper examines the issue of sexual harassment in U.S. colleges and universities through the framework of cultural capital theory. It argues that professors’ cultural capital — comprising academic prestige, research accomplishments, and social networks — empowers them to commit sexual harassment with minimal repercussions. The hierarchical relationship between professors and students, particularly at the graduate level, creates an environment where students depend on professors for academic and career advancement, making them vulnerable to harassment and less likely to report it. The paper highlights the role of gender inequality and the academic power structure in normalizing harassment and silencing victims. Through case studies at institutions like Caltech and Dartmouth College, the paper illustrates how professors’ cultural capital allowed them to evade accountability, while students were pressured into silence. By applying Bourdieu’s theory of cultural capital, the paper concludes that the unequal distribution of cultural capital in higher education contributes significantly to the concealment of sexual harassment and suggests that reforming university monitoring systems may offer a potential solution to address these issues.